Nadia, Nadie - Garrido, Nuria Gómez (Spain : HFF Münich, 2007)
Nadia, after discovering that her husband married a second woman, decided to start a new life alone. Her five daughters mean the world to her and with strength and perseverance she struggles to make it on her own.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films